HUBUNGAN KECEMASAN ORANG TUA DENGAN RESPON FISIOLOGIS BAYI PREMATUR DI RUANG NICU RUMAH SAKIT UMUM DAERAH MOKOPIDO KABUPATEN TOLITOLI - Subroto, Delvin Indayani; Hamdiyah, Hamdiyah; Syukri, Muhammad; Rustam, Husnul Khotimah; Ariyana, Ariyana (Jurnal Kesehatan, 2025)
Premature babies are babies born with a body weight of <2500 grams or with a gestational age of <37 weeks. Premature babies will be treated separately from their mothers/parents, which will limit physical contact between the baby and the mother/father. This can cause anxiety in the mother. Mothers with premature babies are vulnerable to the risk of psychological stress and postpartum depression. This study aims to determine whether there is a relationship between anxiety of parents of premature babies and physiological responses of premature babies. This study is a quantitative study using a cros sectional approach. With a population of all mothers with premature babies who were treated in the NICU room at Mokopido Tolitoli Hospital in February to April, with a total sample of 42 people taken by Accidental Sampling technique. The type of data collection was done by distributing questionnaires to respondents. Bivariate analysis in this study using chi square test. Based on the results of research conducted at the Mokopido Tolitoli Regional General Hospital on the relationship between anxiety and the physiological response of premature infants in the NICU room of the Mokopido Hospital, Toli-toli Regency, it can be concluded that there is a significant relationship in this study, where a significant relationship is obtained between the two variables, namely parental anxiety with the physiological response of infants in the NICU room of the Mokopido Hospital, Tolitoli Regency with a p value where parental anxiety with the baby's heart rate response, namely the heart rate response of the baby